Langsa Multicultural Heritage Virtual Tour : Development of Diversity Literacy Media for Strengthening Global Diversity Awareness - Riyani, Mufti; Hanafiah, Hanafiah; Rahman, Aulia; Aprilia, Rapita; Dewi, Intan Purnama (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This research aims to develop a learning media for the Langsa Multicultural Heritage Virtual Tour to strengthen students' awareness of global diversity. The study used a Research and Development (RnD) method with the 4-D model, which consisted of the stages of Define, Design, Develop, and Disseminate. The subject of this study was grade VII students at SMPN 13 Langsa City, with the consideration that this school is located in a transition area from a school in an urban area to a coastal area with multicultural characteristics. The instruments used included documentation studies, expert validation sheets, and student response questionnaires. Documentation studies were used to analyze curriculum documents and learning outcomes, while expert validation sheets evaluated the suitability of content, design, and practicality. The student response questionnaire, based on a Likert scale, measured the practicality, appeal, and effectiveness of the developed media. Data were analyzed using qualitative and quantitative descriptive techniques, such as expert feedback, tabulation, percentage calculations, and t-tests. The results indicated that the validation test of material experts yielded 86.6% in the very feasible category, and the media expert test yielded 96.6% in the very feasible category. The practicality test resulted in 99.6%, which is very good, the teacher's response was 95.5% in the very good category, and the student response was 93.3% in the very feasible category. The t-test results showed a calculated value of 5.2 with a p-value = 0.000 < 0.05, indicating a significant increase in global diversity knowledge after media treatment.